Between concept and the metaphor: resilience as an approach of human beings from the physics of materials - Thaís Seltzer Goldstein (O Mundo da Saúde)
The present article stems from a personal memory and then presents the origin of the concept of resilience and discusses the implications of its transposition from the field of the Physics of materials to the one of Human Sciences. We propose an analogy between the concept of resilience and the one of social action as presented by Hannah Arendt, in view of contemporary world problem and the ethical commitment of Psychology as regards the promotion of resilience guided not only by subjective transformations but also by social ones.